Orientamento educativo e disuguaglianze di fronte all’istruzione universitaria in Italia: risultati da un esperimento randomizzato - Giovanni Abbiati; Gianluca Argentin; Giulia Assirelli; Carlo Barone; Antonio Schizzerotto (Quaderni di Sociologia, 2017)
The participation in tertiary education in Italy is characterised by sharp vertical and horizontal inequalities, linked to social origins, and by a marked mismatch between the demand for skilled jobs and the distribution of graduates across fields of study. These two problems may derive from the lack of information about the profitability of the investment in tertiary education among students and families. We explored this issue by designing a counselling intervention to provide high school seniors with up-dated and high-quality information about costs of university and post-secondary vocational courses attendance, occupational returns guaranteed by the various fields of study and the chances of successfully completing them. We tested the effect of our initiative on high school senior students’ decisions to enrol either at university or post-secondary vocational courses through a randomized controlled trial. It started in October 2013 and involved about 9,000 students from 62 schools in the provinces of Milan, Vicenza, Bologna and Salerno. We found that treated students did not increase their participation in tertiary education compared to that of control students. However, they were induced to change their initial choice of the field of study moving away from those poorly rewarding towards either highly rewarding ones (students from advantaged families) or post-secondary vocational education (students from disadvantaged families). We explained these effects resorting the rational action theory models.